(untitled) (European Journal of Behavioral Sciences, 2025)
Office workers today are increasingly struggling with stress and poor sleep; poor ergonomic conditions are a big reason for this. Workspaces that aren’t designed well can interrupt a person’s circadian rhythm, increasing stress levels and worsening sleep quality. This study collected data from 73 office workers in India through the Perceived Stress Scale, BOSSA Time-Lapse survey, and Pittsburgh Sleep Quality Index. The results showed that younger workers and those with less experience struggled more with stress and sleep, probably because they’re not yet great at handling work pressures. People in consultancy jobs seemed to have it worse than those in IT, reporting higher stress levels and worse ergonomic conditions. A strong link was found between stress and bad sleep; poor ergonomics also seemed to worsen sleep quality. These findings point to the need for offices to be more ergonomic to keep employees healthy and productive.